Contribution to the study of the urban development north of Seville’s first wall. Morphogenesis of the area within the streets Feria, Perís Mencheta y la Alameda de Hércules. - Miguel Torres García (Medievalista)
This paper sets out more plausible a hypothesis than those formulated to the moment regarding the early development of the urban tissue enclosed amidst Seville’s streets Feria, Castelar, Pasaje Morgado, Perís Mencheta and the Alameda de Hércules. It is grounded on a historical approach, supported by archaelogical, topographic and geological data in order to identify its origins as an Islamic Seville’s suburb destined to industrial activities, which took shape between mid 9th century and the construction of the almoravid-almohad wall. Consequently it defends the hypothesis of Bab al Hadid gate being opened by command of Abd al Rahman II on the Imperial Roman wall in the whereabouts of San Juan de la Palma Square.